DEVELOPMENT AND STUDY OF AN ANTI-CAKING ADDITIVE TO IMPROVE THE PHYSICO-MECHANICAL PROPERTIES OF AMMONIUM NITRATE - Isakov, Burkhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the results of developing and studying a domestic anti-caking additive “Anti-Stick” designed to improve the physico-mechanical properties of ammonium nitrate, reducing its caking, dust formation, and agglomeration during storage. A comparative performance analysis of the developed composition and the imported reagent “Novoflow 3047”, traditionally used in chemical industries, was conducted. The developed additive consists of industrial oil, technical paraffin, technical stearic acid T3, and a surface-active agent in optimized proportions. Experimental results confirmed that the use of “Anti-Stick” reduces caking by 75–85%, decreases dust formation by 1.8–2 times, improves flowability, and enhances the stability of granules during storage.